Role of CD4 molecule in the induction of interleukin 2 and interleukin 2 receptor in class II major histocompatibility complex-restricted antigen-specific T helper clones. T cell receptor/CD3 complex transmits CD4-dependent and CD4-independent signals. - Oyaizu, N (1992)
The CD4 molecule plays an essential role in antigen-induced activation of T helper (Th) cells, but its contribution to signal transduction events resulting in physiologic T cell function is ill defined. By utilizing anti-CD4 monoclonal antibodies (MAbs) that recognize distinct epitopes of CD4, we have investigated the role of CD4 molecule in antigen-induced interleukin 2 (IL-2) and IL-2 receptor (IL-2R) alpha chain expression in class II major histocompatibility complex-restricted antigen-specific human Th clones. Pretreatment of the Th clones with Leu3a resulted in a dose-dependent suppression of antigen-induced proliferative responses, inositol phosphate accumulation, increase in free cytoplasmic calcium ions ([Ca2+]i), IL-2 mRNA accumulation, IL-2 secretion, and membrane IL-2R expression. IL-2R mRNA accumulation, however, was unaffected even at highest Leu3a concentrations. Leu3a treatment did not affect bypass activation of T cells with PMA plus ionomycin or activation via CD2 molecule. The MAb OKT4, which binds another domain of CD4, was not inhibitory. These results suggest that after T cell antigen receptor-CD3 activation, IL-2 gene induction, IL-2 secretion, and membrane IL-2R expression are absolutely dependent upon participation of CD4 molecules, phosphatidylinositol (PI) hydrolysis, and increase in [Ca2+]i. The requirement for IL-2R gene induction, however, occurs independently of CD4 molecule participation and PI hydrolysis.